Chemical changes of soil and water in hillside areas under intensive horticulture - Silva, Laércio S. [UNESP]; Galindo, Izabel C. de L.; Gomes, Romário P. [UNESP]; Campos, Milton C.C.; de Souza, Edivan R.; da Cunha, José M. (FapUNIFESP (SciELO), 2018)
Inadequate and intensive management of soils can promote changes in their chemical attributes and impair the quality of surface and groundwater, especially in hillside areas. Therefore, the aim of this study was to identify possible changes in soil and water chemical composition of hillside areas cultivated with horticulture. For this, chemical attributes of three soil depths (0-10, 10-30, and 30-60 cm) were determined in three hillside positions (upper, middle, and lower thirds) of five hillside and adjacent forest areas, as well as water from reservoirs for agricultural use and human consumption. Compared with the forest area, horticultural areas present soil with lower organic matter content and CEC, but higher values of pH, base saturation, and contents of P, Ca, and K. In cultivated areas, CEC decreases from the upper to the lower hillside, without significant changes in other soil fertility parameters. Soil fertility decreases with depth, regardless of soil management and hillside position. Water from reservoirs adjacent to hillside areas with horticulture is more acidic and has a higher nitrate content, especially during rainy periods.
Keywords: Environmental contamination; Irrigation water; Landscape; Management practices